Long-term Effects of Pediatric Burns on the Circulatory System. - Duke, J.; Randall, S.; Fear, M.; Boyd, James; Rea, S.; Wood, F. (2015)
BACKGROUND: The systemic responses to burns (in particular, elevated levels of catecholamines and stress hormones) have been shown to have an impact on cardiac function for at least 3 years in children with burns. However, it is not clear if these changes lead to long-term effects on the heart. The aim of this study was to assess whether pediatric burn injury is associated with increased long-term hospital use for circulatory diseases. METHODS: A population-based longitudinal study was undertaken using linked hospital and death data from Western Australia for children younger than 15 years when hospitalized for a first burn injury (n = 10?436) in 1980-2012 and a frequency matched noninjury comparison cohort, randomly selected from Western Australia's birth registrations (n = 40?819). Crude admission rates and cumulative length of stay for circulatory diseases were calculated. Negative binomial and Cox proportional hazards regression modeling were used to generate incidence rate ratios and hazard ratios, respectively. RESULTS: After adjustment for demographic factors and preexisting health status, the burn cohort had 1.33 (incidence rate ratio) times (95% confidence interval [CI]: 1.08-1.64) as many circulatory system hospitalizations, 2.26 times the number of days in hospital with a diagnosis of a circulatory disease (2.26, 95% CI: 1.06-4.81), and were at a higher risk of incident admissions (hazard ratio 1.22, 95% CI: 1.03-1.46), compared with the uninjured cohort. CONCLUSIONS: Children who sustain burn injury experience elevated hospital admission rates and increased length of hospital stay for diseases of the circulatory system for a prolonged period of time after burn discharge.